2017
DOI: 10.1017/s0022149x1700116x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating host–parasite co-adaptation relationships involving Angiostrongylus costaricensis

Abstract: Angiostrongylus costaricensis is a parasite that infects rodents, including the wild cotton rat Sigmodon hispidus and pygmy rice rats Oligoryzomys spp., among others. However, urban Rattus norvegicus and Mus musculus have not been identified as important hosts of A. costaricensis. In this study, Swiss mice (SW), Wistar R. norvegicus (RN), wild Oligoryzomys nigripes (ON) and a local strain of M. musculus (RGS) were experimentally infected with A. costaricensis. Survival, elimination of L1 (total sum per group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Similar findings were previously reported by Hermes et al (2018), who showed that survival was longer among mice infected with five L3 of A. costaricensis than among those infected with higher doses, as was the time to eliminate L1 in faeces. These findings indicate that it is possible to inoculate mice with lower doses in order to maintain the life cycle of the parasite in animal facilities, despite the high mortality rates reported (Garrido et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were previously reported by Hermes et al (2018), who showed that survival was longer among mice infected with five L3 of A. costaricensis than among those infected with higher doses, as was the time to eliminate L1 in faeces. These findings indicate that it is possible to inoculate mice with lower doses in order to maintain the life cycle of the parasite in animal facilities, despite the high mortality rates reported (Garrido et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Mice infected with 15 L3 have been shown to die sooner than do those infected with 30 L3 (Hermes et al , 2018). The genetic variability of each mouse and its resistance to infection are also factors that affect survival (Ishih & Sano, 1989; Garrido et al , 2017). Our histopathological findings contribute to elucidating these temporal differences.…”
Section: Discussionmentioning
confidence: 99%
“…Parasitological diagnosis is not an option in angiostrongyliasis, since larvae in feces was never consistently detected in AA patients and only rarely documented in cerebrospinal fluid in eosinophilic meningitis. 6 Development of immunological methods have faced two main difficulties: (i) large production of antigens is laborious and it depends on in vivo maintenance of parasites, especially for A. costaricensis , which shows less than optimal adaptability to laboratory mice strains; 7 (ii) lack of a large reference panel of sera with precise characterisation of true-positive samples by histopathology. Complicated abdominal angiostrongyliasis leading to biopsy or anatomopathological examination and identification of the parasite is not frequent.…”
mentioning
confidence: 99%